Variability of particulate bioavailable phosphorus, particulate organic carbon and nitrogen in agricultural and urban rivers. Issue 3 (June 2019) - Mbabazi, James; Inoue, Takanobu; Yokota, Kuriko; Saga, Makoto
Highlights: PBAP, POC and PON were evaluated in an agricultural and urban river. POC and PON concentrations in both rivers declined at high flow possibly due to alteration in particulate organic matter composition. POC to PON ratios of SS reveal the change in the nature of particulate organic matter. PBAP exhibited a positive relationship with POC and PON concentration in both rivers indicating that particulate organic matter contributes to BAP. Abstract: Suspended sediments (SS) play a key role as carriers of particulate nutrients which support primary productivity in aquatic systems. In this study, we assessed the relationship between particulate bioavailable phosphorus (PBAP), particulate organic carbon (POC) and particulate organic nitrogen (PON) in rivers flowing through contrasting land use at high and low flow. PBAP as a percentage of particulate phosphorus varied from 5 to 54%, and at low flow, there was a significant increase in PBAP fraction in the urban river as compared to the agricultural river. In addition, elevated POC and PON concentrations in both rivers were associated with low flow. POC and PON concentrations in both rivers declined at high flow presumably due to the mixing effects of water from different sources in the watershed which could have altered the particulate organic matter composition. A significant correlation existed between POC and SS in both rivers, and POC to PON ratios of SS from the rivers point to the change in the nature of particulate organic matter at varying flow conditions. PBAP exhibited a positive relationship with POC and PON concentration in both rivers possibly an indication that particulate organic matter contributes to bioavailable phosphorus in the rivers.